Analysis of mandibular premolar root position in relation to adjacent cortical plates and mental foramen using cone beam computed tomography in the Saudi population - Aldosimani, Mazen A. (Saudi Med J, 2019)
OBJECTIVES: To evaluate the horizontal and vertical location of the mental foramen (MF), as well as the relationship of lower premolars to buccal and lingual cortical plates using cone beam computed tomography (CBCT). METHODS: Retrospective cross-sectional study conducted using CBCT scans that were obtained between early 2014 and late 2016 from King Saud University Dental hospital database in Riyadh, Kingdom of Saudi Arabia; 94 patients (53 males and 41 females) were included. Three examiners independently performed one-sided measurements for each patient. Data analyzed statistically and a p<0.05 was considered significant. RESULTS: The mean distances from the outer boundary of the buccal cortex to the first and second premolars (R1) were 1.55 mm and 1.98 mm. The mean distances from the outer boundary of the lingual cortical plate to the first and second premolars (R2) were 4.06 mm and 4.73 mm. The respective mean total bone thicknesses, including the roots of the first and second premolars (R3), were 9.32 mm and 10.08 mm. The mean distance between the MF and the mandibular second premolar apex was 3.13 mm. CONCLUSION: Mandibular premolars are in close proximity to MF especially mandibular second premolar. Presurgical assessment is essential when surgical treatment is planned at this area.